Alternativas en el manejo del chinche del arroz (Oebalus insularis) con la utilización de una fuente de microorganismos eficientes en el cultivo de arroz (Oryza sativa L.) en el cantón Mocache – Los Ríos - Ecuador. - Ramírez Coello, Edison Leonel (2018)
The objective of this study was the effect of efficient microorganisms applied in different doses for the control of bedbugs in rice cultivation. The trial was carried out at the "La María" Experimental Farm, owned by the State Technical University of Quevedo, at Km 7 of the Quevedo - El Empalme road, Los Ríos province. Five treatments were studied: three formed by the doses of efficient microorganisms (20, 40 and 60 l/ha), a definitive control by the application of Chlorpyrifos. Based on the results obtained, the results in the study were not influenced on the weight of 1000 grains with a general average of 34.0 g. Both the treatments of efficient microorganisms and the application of Chlorpyrifos showed less time to flowering (54.3 to 54.5 days) than the absolute control that registered an average of 57.9 days, product of a lower interference in the development of the plants by attack of the bedbugs. When Chlorpyrifos was present, more healthy seeds were obtained with 108.5 grains per spike, and at the same time less empty grains (8.20) and less stained grains (8.1), followed by the application of 40 l/ha of efficient microorganisms than 94.2 healthy grains, 10.6 vain grains and 11.7 stained grains (80.9, 9.1% and 10.0% with respect to the total grains per spike of 116.5 grains.) The most efficient treatment for bedbugs control was Chlorpyrifos, which controls 85.0% of the bedbugs present (11.3 chinches controlled of 13.3 present before treatment), however, the application of 40 l/ha of efficient microorganisms allowed the control of 83.8% of the 11.1 bedbugs present before treatment (9.3 controlled specimens) .When applied 40 l/ha of efficient microorganisms gave a yield of only 239.6 Kg /ha below the yield obtained with Chlorpyrifos (4614.6 Kg/ha) which was the highest observed with 72.07%, followed by the treatment of 40 l/ha of efficient microorganisms with 63.19%. Keywords: rice cultivation, efficient microorganisms, bed bug control